Negative electrode composite material and preparation method thereof, negative electrode plate and lithium ion battery

By using the combination technology of lithium polyacrylate and amorphous carbon in lithium-ion batteries, a secondary particle structure with micron-scale pores and heating the coating layer, the structural stability and expansion rate of silicon carbon negative electrode materials are solved, and the improvement of the structural stability and expansion rate of silicon carbon negative electrode materials are improved. The cycle stability and service life of the battery are achieved.

CN119252885APending Publication Date: 2025-01-03ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317638.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The structural stability and expansion rate of silicon carbon anode materials in existing lithium-ion batteries are poor, resulting in insufficient cycle stability and service life, and it is difficult for existing processes to effectively reduce expansion rate.

Method used

By combining lithium polyacrylate and amorphous carbon, the structural stability of the material is improved by forming a secondary particle structure with micron-scale pores, and the silicon carbon particles are tightly coated, and the carbon coating is formed by heating the coating layer to improve the structural stability of the material and Processing performance.

Benefits of technology

It effectively alleviates the expansion of pore space between particles, avoids crushing, improves the structural stability and processing performance of the material, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252885A_ABST
    Figure CN119252885A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a negative electrode composite material and a preparation method thereof, a negative electrode plate and a lithium ion battery. The negative electrode composite material comprises an inner core and a functional coating layer arranged on the outer surface of the inner core, the functional coating layer comprises lithium polyacrylate coating the outer surface of the inner core; the inner core comprises silicon carbon particles and a binder; the silicon-carbon particles are connected through the binder to form secondary particles with pores of more than micron order. According to the invention, the expansion degree of the pore space among the particles can be reduced, and phenomena such as crushing can be avoided, so that the structural stability of the material and the processing performance of the material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a negative electrode composite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art

[0002] With the rapid development of global industrialization, the large-scale use of fuel vehicles has caused serious air pollution problems. In particular, the exhaust emissions from fuel vehicles have not only exacerbated the deterioration of urban air quality, but also posed a major threat to human health. Therefore, governments and environmental protection organizations have begun to focus on environmental pollution control and actively promote the use of green energy and new energy vehicles to reduce dependence on fossil fuels and pollutant emissions.

[0003] In the field of new energy vehicles, lithium-ion batteries have become the mainstream power source for electric vehicles due to their high energy density, low self-discharge rate, and high charging efficiency. However, current lithium-ion battery technology still faces challenges such as long charging time and limited driving range, which to some extent restricts the popularity and development of electric vehicles. Therefore, the development of a new battery material that can charge quickly and provide long driving range is crucial to promoting the development of the electric vehicle industry.

[0004] Both graphite and silicon can be used as one of the most commonly used negative electrode materials in lithium-ion batteries. The improvement of the energy density of negative electrode materials has been a research hotspot in the field of scientific research in recent years. However, silicon materials face many problems in practical applications: 1) First, during the lithium insertion process, lithium-silicon alloys expand and break particles due to material expansion, and lithium-silicon alloys react with electrolytes to form a large number of byproducts, which will seriously affect the cycle stability and service life of the battery; 2) Secondly, the existing deposited silicon-carbon negative electrode materials have poor ion conductivity due to the poor intrinsic electronic conductivity of silicon and the multiple interfaces encountered by lithium ions during the conduction process of porous carbon-silicon-porous carbon interfaces; 3) Furthermore, some existing negative electrode materials use polymers, inorganic substances, etc. coated on the outside of silicon materials to inhibit expansion, but the inhibitory effect on expansion is not good. In addition, the current material-side treatment methods for reducing the material expansion rate are generally concentrated on the process, specifically reducing the synthesis of silicon carbide and enhancing the uniformity of silicon deposition; but the process is difficult and the degree of reduction is limited. Therefore, improving expansion from the perspective of structural design is a novel and more promising way. In view of this, it is indeed necessary to provide a technical solution to the above problems.

[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a negative electrode composite material to address the problems of poor structural stability and excessive expansion rate of existing silicon-carbon negative electrode materials in view of the deficiencies in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A negative electrode composite material comprises a core and a functional coating layer arranged on the outer surface of the core; the functional coating layer comprises lithium polyacrylate coated on the outer surface of the core; the core comprises silicon-carbon particles and a binder; the silicon-carbon particles are connected by the binder to form secondary particles with pores above the micrometer level.

[0009] Preferably, the core further comprises a binder, and the functional coating layer further comprises a carbon coating layer coated on the outer surface of the lithium polyacrylate.

[0010] Preferably, the binder is asphalt.

[0011] Preferably, the mass content of the carbon coating layer in the negative electrode composite material is 5-15%; and / or the mass ratio of the binder, the lithium polyacrylate and the carbon coating layer is (1-3): (1-3): (5-10).

[0012] Preferably, the silicon-carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix.

[0013] Preferably, the pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm3.

[0014] Preferably, the pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%).

[0015] In addition, the present invention also provides a method for preparing the above-mentioned negative electrode composite material, comprising:

[0016] S1, heating and carbonizing the raw materials to form a carbon source;

[0017] S2, mixing the carbon source and the pore-forming agent and calcining them to form a porous carbon matrix;

[0018] S3, acid-washing, water-washing and calcining the porous carbon substrate to obtain a purified porous carbon substrate;

[0019] S4, depositing nano-silicon on the purified porous carbon matrix to obtain a porous carbon matrix on which nano-silicon is grown;

[0020] S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product;

[0021] S6, using lithium polyacrylate to perform bonding and coating treatment on the secondary particle product obtained in step S4;

[0022] S7, using carbon material to heat and coat the product obtained in step S6, thereby obtaining the negative electrode composite material.

[0023] Preferably, in step S1, the carbonization temperature is 500°C to 700°C and the carbonization time is 3h to 6h.

[0024] Preferably, in step S4, the deposition reaction temperature is 350° C. to 450° C., and the time is 5 h to 7 h.

[0025] Preferably, in step S5, the temperature of the fusion treatment is 200°C to 400°C.

[0026] Preferably, in step S6, the coating treatment specifically includes: mixing and dispersing lithium polyacrylate and the secondary particle product in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere.

[0027] Preferably, in step S7, the heating coating treatment specifically includes: placing the product of lithium polyacrylate coating treatment in a rotary kiln or a fluidized bed; introducing nitrogen as a carrier gas to transform the product of lithium polyacrylate coating treatment from solid particles into a fluidized state; and then introducing one or more of acetylene, ethylene, and methane to heat and coat at a reaction temperature of 500 to 700°C and a reaction time of 2 to 4 hours to form a composite material with a carbon coating amount of 5% to 15%.

[0028] In addition, the present invention also provides a negative electrode sheet, comprising the negative electrode composite material described above.

[0029] In addition, the present invention also provides a lithium-ion battery, comprising the negative electrode sheet described above.

[0030] The beneficial effect of the present invention is that the technical solution can alleviate the expansion degree of the pore space between the particles through the combined effect of the acrylic layer and the amorphous carbon, and tightly wrap the silicon-carbon particles of the inner shell, thereby avoiding the occurrence of breakage and the like, and effectively improving the structural stability of the material and the performance of material processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the structure of a negative electrode composite material according to an embodiment of the present invention;

[0032] Figure 2 The figure is a flow chart of a method for preparing a negative electrode composite material according to an embodiment of the present invention.

[0033] In the figure: 1-core; 2-functional coating layer; 21-carbon coating layer; 22-lithium polyacrylate. DETAILED DESCRIPTION

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and multiple situations exist alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] The following is combined with Figure 1-2 The present invention is further described in detail, but is not intended to limit the present invention.

[0039] like Figure 1 As shown, in one embodiment of the present invention, the negative electrode composite material comprises a core 1 and a functional coating layer 2 disposed on the outer surface of the core 1: the functional coating layer 2 comprises lithium polyacrylate 22 coated on the outer surface of the core 1; the core 1 comprises silicon-carbon particles and a binder; the silicon-carbon particles are connected by the binder to form secondary particles with pores of micrometer level or above. Among them, the functional coating layer 2 also comprises a carbon coating layer 21 coated on the outer surface of the lithium polyacrylate 22.

[0040] This technical solution can alleviate the expansion of the pore space between particles by combining the acrylic layer and amorphous carbon, and tightly wrap the silicon-carbon particles of the inner shell, thereby avoiding the occurrence of breakage and effectively improving the structural stability of the material and the performance of material processing.

[0041] The binder is asphalt or coal tar or phenolic resin or epoxy resin. Through the fusion reaction between asphalt and silicon-carbon particles, the structure can avoid the nano-silicon particle size being too large or too small to affect the primary effect of the material, thereby improving the stability of the structure and the use efficiency.

[0042] Specifically, in some embodiments, the kernel is formed by carbonizing one or more carbon sources such as resin, petroleum coke and anthracite. That is, the kernel is obtained by carbonizing one or more carbon sources such as coconut shell, rice husk, platycodon and other biomass, resin, petroleum coke and anthracite; thereby, a kernel with enhanced carbon structure stability can be obtained.

[0043] Specifically, in some embodiments, the carbon coating layer accounts for 5-15% of the mass content of the negative electrode composite material. By applying a carbon coating layer with a weight ratio of 10%, 12%, 13%, 14%, or 15% on the outer surface of the inner core, the sealing between the silicon-carbon particles can be effectively improved, and the contact between silicon and the electrolyte can be reduced, which is beneficial to ensure the integrity of the entire structure during the cycle.

[0044] Specifically, in some embodiments, the silicon-carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix; the pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm 3 ; For example, it can be 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 Etc. The reasonable pore volume can effectively control the expansion speed and degree of the interstitial space and improve the stability of the structure.

[0045] Among them, in some embodiments, the pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%). In other words, the distribution ratio of micropores is 90%, the distribution ratio of mesopores is 5%, and the distribution ratio of macropores is 5%; or 92%: 4%: 4% or 94%: 3%: 3%, etc.; through the reasonable ratio of micropores, mesopores and macropores, the expansion speed and degree of the gap space can be effectively controlled to improve the stability of the structure.

[0046] Among the nano silicon particles, the diameter of the first nano silicon particle is less than 2nm; the diameter of the second nano silicon particle is (2-10nm); the diameter of the third nano silicon particle is greater than 50nm; and the content ratio of these three nano silicon particles is (89-91%): (7-9%): (1-4%); for example: it can be 89%: 7%: 4%, 91%: 7%: 2%, etc. This structure is beneficial to the comprehensive coverage of subsequent coating by obtaining a porous carbon matrix of grown nano silicon of different sizes, which can effectively increase the stability of the material structure and reduce the loss of active silicon particles.

[0047] Specifically, in some embodiments, the mass ratio of the binder, the lithium polyacrylate and the carbon coating is (1-3): (1-3): (5-10). When the content of lithium polyacrylate in this structure increases, it is beneficial to suppress expansion, and when the content of the conductive material increases, it is beneficial to eliminate polarization; however, if both the lithium polyacrylate and the conductive material are too much, it will affect the conductivity of the material and reduce the material capacity. And if the amount of the binder is small, it will affect the firmness of the overall structure, and if the amount is too much, it will affect the conductivity of the material and reduce the material capacity.

[0048] The present invention also proposes a method for preparing a negative electrode composite material. The method for preparing a negative electrode composite material is used to prepare a negative electrode composite material. The specific structure of the negative electrode composite material refers to the above embodiment. Since the method for preparing the negative electrode material adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.

[0049] According to a second aspect of the present invention, Figure 2 As shown, the present invention also provides a method for preparing the negative electrode composite material, comprising the following steps:

[0050] S1, heating and carbonizing the raw materials to form a carbon source;

[0051] S2, mixing the carbon source and the pore-forming agent and calcining them to form a porous carbon matrix;

[0052] S3, acid-washing, water-washing and calcining the porous carbon substrate to obtain a purified porous carbon substrate;

[0053] S4, depositing nano-silicon on the purified porous carbon matrix to obtain a porous carbon matrix on which nano-silicon is grown;

[0054] S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product;

[0055] S6, using lithium polyacrylate to perform bonding and coating treatment on the secondary particle product obtained in step S4;

[0056] S7, using carbon material to heat and coat the product obtained in step S6, thereby obtaining the negative electrode composite material.

[0057] The technical solution of the present invention can alleviate the expansion of the pore space between particles and avoid the occurrence of crushing and the like through the combined action of the adsorptive material, the adhesive and the vapor-deposited carbon coating, thereby effectively improving the structural stability of the material and improving the processing performance of the material; and can effectively remove excessive impurities on the surface of the carbon source through the activation pore-forming and purification deposition treatment of the carbon source, thereby improving the structural stability of the product and improving the processing efficiency.

[0058] In some embodiments, in step S1, the temperature of the heating carbonization is 500°C to 700°C; the time of the heating carbonization is 3h to 6h. Further, the raw material is carbonized under the conditions of a heating carbonization temperature of 500°C to 700°C and a duration of 3h to 6h to generate the carbon source. In other words, the raw material is carbonized under a higher temperature (500°C to 700°C; wherein less than 500°C is a lower temperature; greater than 700°C is a higher temperature) and a longer time (3h to 6h; wherein less than 3h is a shorter duration; greater than 6h is a longer duration), while reducing heteroatoms and enhancing the stability of the formed carbon structure, providing a stable structure for subsequent pore formation and porous carbon structure production.

[0059] In some embodiments, in S2, specifically: the carbon source and the pore-forming agent are mixed, and placed in a tubular furnace into which the first mixed gas is passed for calcination to form a porous carbon matrix. That is, the pore-forming agent is at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; the mixing mass ratio of the carbon source to the pore-forming agent is 1:1 to 1:3. The first mixed gas is a mixture of hydrogen and nitrogen, or a mixture of hydrogen and argon; the volume ratio of the two gases in the mixed gas is 1:1 to 1:9, for example, it can be 1:1, 1:2, 1:4, 1:9, etc. Furthermore, the carbon source is mixed with the pore-forming agent of at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; and then placed in a tubular furnace with a mixture of hydrogen and nitrogen, or a mixture of hydrogen and argon for calcination to form a pore-forming product; thus, compared with the current existing technology, by controlling the amount of strong alkali and the corrosion time to corrode the carbon source, a pore distribution structure with a pore volume of 0.5g / cm3 to 0.9g / cm3 and stronger stability can be obtained. The pore distribution structure has 89% to 91% micropores (for example, 89%, 90%, 91%, etc., preferably 90%), 3% to 6% mesopores (for example, 3%, 4.9%, 5%, 6%, etc., preferably 5%), and 3% to 6% macropores (for example, 3%, 4.9%, 5%, 5.1%, 6%, etc., preferably 5%), and has stronger stability; thereby forming a larger proportion of micropores and reducing the proportion of mesopores and macropores, which can avoid excessive coverage of low stress point areas in the porous carbon matrix, thereby ensuring the structural stability of the porous carbon matrix. In addition, 5% of mesopores, 5% of macropores and 90% of micropores can ensure the fusion amount of the asphalt powder binder when the subsequent porous carbon matrix is ​​assembled with the asphalt powder binder; thereby providing a stable structure for subsequent production and ensuring the smoothness and quality of processing.

[0060] In some embodiments, step S3 specifically comprises: acid-washing the porous carbon matrix, washing with water until it is neutral, drying, and calcining to obtain a purified porous carbon matrix; wherein, the pore-forming product is acid-washed. Furthermore, the acid-washing material is hydrochloric acid or the like; the acid-washed product is then neutralized in water so that the pH value reaches 6.6 to 7.3; further, the pH value is preferably 7. That is to say, since more impurities (including other unnecessary atoms) will be generated during the pore-forming process; the impurities are purified by acid dissolution, and then the excess residual alkaline substances or acid-washing substances are washed away by water, and then placed in a tubular furnace and calcined at 1250°C to 1280°C to obtain a porous carbon matrix; thus, the carbon matrix can be purified by high-temperature heating, thereby reducing the presence of other unnecessary atoms, and is beneficial to improving the initial efficiency of the material in battery applications.

[0061] In some embodiments, in S4, specifically: placing the purified porous carbon matrix in a rotary kiln or a fluidized bed, introducing a second mixed gas to deposit nano-silicon inside the porous carbon matrix, and obtaining a porous carbon matrix with grown nano-silicon. The second mixed gas is a mixture of a protective gas and a silicon source gas; further, the protective gas is argon, helium or nitrogen; the deposition reaction temperature is 350°C to 450°C, and the time is 5h to 7h. Furthermore, the purified porous carbon matrix is ​​placed in a rotary kiln or a fluidized bed, and then a protective gas and a silicon source gas are introduced successively to mix with the porous carbon matrix, and silane deposition is carried out under the conditions of a deposition reaction temperature of 350°C to 450°C (for example, 350°C, 380°C, 410°C, 330°C, 450°C, etc.) and a time of 5h to 7h, so that the porous carbon inside can be reduced to nano-silicon; and then a second intermediate product of a porous carbon matrix is ​​obtained, in which 90% of the nano-silicon has a diameter less than 2nm, 8% of the nano-silicon has a diameter of 2-10nm, and 2% of the nano-silicon has a diameter greater than 50nm.

[0062] In some embodiments, in step S5, the temperature of the fusion treatment is 200°C to 400°C (for example, it can be 200°C, 280°C, 310°C, 380°C, 400°C, etc.). Further, the porous carbon matrix and asphalt powder with a particle diameter of 10μm to 50μm are mixed with a mixer for 20 to 30 minutes to obtain a mixed intermediate material; and the mixed intermediate material is subjected to a fusion treatment at 200°C to 400°C to obtain a secondary particle product; thereby, the gaps between the secondary particle products can alleviate expansion, thereby improving the stability of the structure. When the fusion temperature is too low, the porous carbon matrix has more surface functional groups, resulting in low first efficiency; when the fusion temperature is too high, the nano-silicon particle size will increase; however, the material expands greatly and is prone to generate inert silicon carbide, thereby losing active silicon and having poor kinetic properties. The medium-temperature asphalt fusion temperature is moderate, which will neither reduce the first effect of the material nor generate silicon carbide. When the amount of asphalt powder is too large, the primary efficiency of the material is reduced; when the amount of asphalt powder is too small, secondary particles are difficult to form, and micron-sized pores between particles are difficult to form.

[0063] In some embodiments, the bonding coating treatment specifically includes: mixing and dispersing lithium polyacrylate and secondary particle products in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere. Further, the secondary particle product and the adhesive of lithium polyacrylate (PAA-Li) are placed in a stirring cylinder and stirred and mixed at 800r / min for 1h to form a mixed slurry; then the mixed slurry is placed in a spray drying container, and the mixed slurry is sprayed at a spray speed of 700-800r / min and blown dry at a wind speed of 10L / min under a protective atmosphere; thereby, the particle expansion and crushing are alleviated through the adhesion of PAA-Li, thereby improving the integrity of the entire structure and improving the cycle stability of the battery cell. When the amount of PAA-Li is too much, the kinetic properties of the material will be reduced. When the amount of PAA-Li is too little, the expansion cannot be effectively alleviated.

[0064] In some embodiments, in step S7, the reaction temperature of the heating coating is 500-700°C (for example, it can be 500°C, 580°C, 610°C, 630°C, 700°C, etc.), and the reaction time is 2-4h. The product coated with lithium polyacrylate is placed in a rotary kiln or a fluidized bed; nitrogen is introduced as a carrier gas to transform the product coated with lithium polyacrylate from solid particles to a fluidized state; then one or more of acetylene, ethylene, and methane are introduced to heat and coat at a reaction temperature of 500-700°C and a reaction time of 2-4h, thereby forming a composite material with a carbon coating amount of 5% to 15%. Furthermore, when the reaction gas is two of acetylene, ethylene, and methane, the ratio between any two is 1:1; when the reaction gas is three of acetylene, ethylene, and methane, the ratio between the three is 1:1:1.

[0065] According to a third aspect of the present invention, the present invention further provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the above-mentioned negative electrode composite material.

[0066] According to a fourth aspect of the present invention, the present invention further provides a lithium-ion battery, comprising a battery cell and an electrolyte formed by stacking or winding a positive electrode sheet, a separator and a negative electrode sheet in sequence, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0067] Example 1

[0068] Preparation of negative electrode composite materials:

[0069] 1. Carrying out carbonization treatment on anthracite at a temperature of 700° C. and for 6 hours to generate the carbon source;

[0070] 2. Mixing the carbon source with the pore-forming agent of lithium hydroxide, and calcining in a tubular furnace into which a mixture of hydrogen and argon in a volume ratio of 1:1 is introduced to form a porous carbon matrix;

[0071] 3. The porous carbon matrix is ​​acid-washed (with hydrochloric acid), then washed with water until neutral, dried, and calcined to obtain a purified porous carbon matrix;

[0072] 4. Place the purified porous carbon matrix in a rotary kiln or a fluidized bed, then introduce argon gas and silicon source gas into the porous carbon matrix in turn, and perform silane deposition at a deposition reaction temperature of 400° C. for 6 hours;

[0073] 5. The porous carbon matrix after silane deposition treatment and asphalt powder with a particle diameter of 40 μm are mixed in a mixer for 28 minutes to obtain a mixed intermediate material; and the mixed intermediate material is subjected to a fusion treatment at 380°C to obtain a secondary particle product; wherein the amount (%) of medium-temperature asphalt of 200°C is 2%; wherein 200°C to 400°C is medium temperature, greater than 400°C is high temperature; less than 200°C is low temperature;

[0074] 6. The secondary particle product and lithium polyacrylate (PAA-Li) are placed in a stirring tank and stirred at 800 r / min for 1 hour to form a mixed slurry; the mixed slurry is then placed in a spray drying container, and the mixed slurry is sprayed at a spray speed of 800 r / min and air-dried at a wind speed of 10 L / min under nitrogen; wherein the amount (%) of PAA-Li used is 2%;

[0075] 7. Place the product coated with lithium polyacrylate in a rotary kiln or a fluidized bed; introduce nitrogen as a carrier gas to transform the product coated with lithium polyacrylate from solid particles into a fluidized state; then introduce acetylene to heat and coat the product at a reaction temperature of 600° C. and a reaction time of 3 h, thereby obtaining a carbon-coated material with an amount (%) of 10%;

[0076] After testing, the expansion rate of the composite material obtained in this embodiment is 80%; the processing performance (gas production in room temperature water for 48 hours, mL / kg) is 100; the capacity (1.5V, mAh / g) is 1800; the first efficiency of the composite material (1.5v, %) is 91.0%; and the capacity retention rate of 500mAh / g blended gram-capacity cycle (500cls) is 86%.

[0077] Preparation of negative electrode:

[0078] The negative electrode composite material, conductive agent (carbon nanotubes) and binder (PAA) prepared above were mixed in a mass ratio of 98:1:1 to prepare a negative electrode slurry, the negative electrode slurry was coated on the current collector copper foil, dried at 85°C and then cold pressed, and then trimmed, cut and stripped, and then dried at 85°C under vacuum conditions, and the copper-nickel-plated tabs were welded to prepare a negative electrode sheet.

[0079] Preparation of lithium-ion batteries:

[0080] The negative electrode sheet, separator (PP), and positive electrode sheet (nickel cobalt manganese oxide positive electrode) prepared above are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, and the prepared electrolyte is injected into the dried battery, and the battery is packaged, allowed to stand, formed, shaped, and capacity divided to complete the preparation of the lithium-ion battery.

[0081] Example 2

[0082] The only difference between Example 2 and Example 1 is that the amount (%) of asphalt used in the preparation is 1%.

[0083] Example 3

[0084] The only difference between Example 3 and Example 1 is that the amount (%) of asphalt used in the preparation is 3%.

[0085] Example 4

[0086] The only difference between Example 4 and Example 1 is that the amount (%) of PAA-Li used in the preparation is 1%.

[0087] Example 5

[0088] The only difference between Example 5 and Example 1 is that the amount (%) of PAA-Li used in the preparation is 3%.

[0089] Example 6

[0090] The only difference between Example 6 and Example 1 is that the amount (%) of carbon coating material used in the preparation is 5%.

[0091] Example 7

[0092] The only difference between Example 7 and Example 1 is that the amount (%) of carbon coating material used in the preparation is 15%.

[0093] Example 8

[0094] The only difference between Example 8 and Example 1 is that the amount (%) of 100°C low-temperature asphalt used is 2%.

[0095] Example 9

[0096] The only difference between Example 9 and Example 1 is that the amount (%) of 500°C high-temperature asphalt used is 2%.

[0097] Example 10

[0098] The only difference between Example 10 and Example 1 is that the amount (%) of the medium-temperature phenolic resin at 200°C is 2%.

[0099] Comparative Example 1

[0100] The only difference between Comparative Example 1 and Example 1 is that no asphalt is used.

[0101] Comparative Example 2

[0102] The only difference between Comparative Example 2 and Example 1 is that PAA-Li is not used.

[0103] Comparative Example 3

[0104] The only difference between Comparative Example 3 and Example 1 is that no carbon coating material is used.

[0105] Comparative Example 4

[0106] The only difference between Comparative Example 4 and Example 1 is that no carbon coating material and PAA-Li are used.

[0107] Comparative Example 5

[0108] The only difference between Comparative Example 5 and Example 1 is that no carbon coating and asphalt are used.

[0109] Comparative Example 6

[0110] The difference between Comparative Example 6 and Example 1 is that no asphalt and PAA-Li are used, and the amount of carbon coating material used is 10%.

[0111] Comparative Example 7

[0112] The only difference between Comparative Example 7 and Example 1 is that no carbon coating material, asphalt and PAA-Li are used.

[0113] Comparative Example 8

[0114] The only difference between Example 8 and Example 1 is that the amount (%) of asphalt used in the preparation is 4%.

[0115] Comparative Example 9

[0116] The only difference between Example 9 and Example 1 is that the amount (%) of asphalt used in the preparation is 0.3%.

[0117] Electrochemical performance tests were performed on the negative electrode sheets and lithium-ion batteries prepared in the above embodiments and comparative examples, respectively. The test results are shown in Tables 1-2.

[0118] Table 1

[0119]

[0120]

[0121] Table 1

[0122]

[0123] From the test results in Table 1 and Table 2 above, we can see that:

[0124] 1. After secondary granulation alone, the secondary particle structure cannot be maintained due to the large expansion of silicon during the cycle, which is equivalent to no secondary granulation. The combination of secondary granulation and binder can maintain the structure of secondary particles, always maintain a complete secondary particle structure during the cycle, and inhibit material expansion when lithium is embedded. Finally, the composite carbon coating material is used to strengthen the assembly between particles, which can reduce material polarization, thereby inhibiting expansion and increasing cycle life.

[0125] 2. During the production and processing, the optimal amount of asphalt used in the production is 2%, the optimal amount of PAA-Li is 2%, and the amount of carbon coating is 10% to 15%; thus, the deposited silicon-carbon can be secondary granulated by a suitable amount of asphalt, so that multiple deposited silicon-carbon particles adhere together to form a small whole, and the expansion of voids can be alleviated; and the silicon-carbon particles can be tightly coated with a suitable amount of asphalt, PAA-Li and the outer carbon layer together, which can increase the structural stability of the material.

[0126] In summary, the negative electrode composite material provided by the present invention alleviates particle expansion and breakage through the adhesion effect of lithium polyacrylate, and combined with the coating effect of CVD carbon coating, it can reduce the contact between silicon and electrolyte during the use of the negative electrode composite material, thereby increasing the structural stability of the material; thereby effectively alleviating the expansion of gaps between secondary particles, avoiding breakage of particles due to excessive expansion, thereby achieving a perfect composite of carbon and silicon, and enhancing the cycle stability of the material and improving the safety of use.

[0127] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode composite material, characterized in that: It comprises an inner core and a functional coating layer arranged on the outer surface of the inner core; the functional coating layer comprises lithium polyacrylate coated on the outer surface of the inner core; the inner core comprises silicon-carbon particles and a binder; the silicon-carbon particles are connected by the binder to form secondary particles with pores above the micron level.

2. The negative electrode composite material according to claim 1, characterized in that: The functional coating layer also includes a carbon coating layer coated on the outer surface of the lithium polyacrylate.

3. The negative electrode composite material according to claim 2, characterized in that: The binder is asphalt or coal tar or phenolic resin or epoxy resin.

4. The negative electrode composite material according to claim 1, characterized in that: The mass content of the carbon coating layer in the negative electrode composite material is 5% to 15%; and / or the mass ratio of the binder, the lithium polyacrylate and the carbon coating layer is (1 to 3): (1 to 3): (5 to 10).

5. The negative electrode composite material according to claim 1, characterized in that: The silicon-carbon particles include a porous carbon matrix and nano-silicon particles deposited inside the porous carbon matrix.

6. The negative electrode composite material according to claim 5, characterized in that: The pore volume of the porous carbon matrix is ​​0.5 to 0.9 g / cm3.

7. The negative electrode composite material according to claim 5, characterized in that: The pores of the porous carbon matrix include micropores, mesopores and macropores, and the distribution ratio of the micropores, mesopores and macropores is (88-94%): (3-6%): (3-6%).

8. A method for preparing a negative electrode composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, heating and carbonizing the raw materials to form a carbon source; S2, mixing the carbon source and the pore-forming agent and calcining them to form a porous carbon matrix; S3, acid-washing, water-washing and calcining the porous carbon substrate to obtain a purified porous carbon substrate; S4, depositing nano-silicon on the purified porous carbon matrix to obtain a porous carbon matrix on which nano-silicon is grown; S5, mixing the product obtained in step S4 with a binder and performing a fusion treatment to form a secondary particle product; S6, using lithium polyacrylate to perform bonding and coating treatment on the secondary particle product obtained in step S4; S7, using carbon material to heat and coat the product obtained in step S6, thereby obtaining the negative electrode composite material.

9. The method for preparing the negative electrode composite material according to claim 8, characterized in that: In step S1, the heating carbonization temperature is 500°C to 700°C, and the time is 3h to 6h.

10. The method for preparing the negative electrode composite material according to claim 8, characterized in that: In step S4, the deposition reaction temperature is 350° C. to 450° C., and the time is 5 h to 7 h.

11. The method for preparing the negative electrode composite material according to claim 8, characterized in that: In step S5, the temperature of the fusion treatment is 200°C to 400°C.

12. The method for preparing the negative electrode composite material according to claim 8, characterized in that: In step S6, the bonding and coating treatment specifically includes: mixing and dispersing lithium polyacrylate and the secondary particle product in an aqueous solvent to form a mixed slurry, and spray drying the mixed slurry under a protective atmosphere.

13. The method for preparing the negative electrode composite material according to claim 8, characterized in that: In step S7, the heating coating treatment specifically includes: placing the product of lithium polyacrylate coating treatment in a rotary kiln or a fluidized bed; introducing nitrogen as a carrier gas to transform the product of lithium polyacrylate coating treatment from solid particles into a fluidized state; and then introducing one or more of acetylene, ethylene, and methane to heat and coat at a reaction temperature of 500 to 700°C and a reaction time of 2 to 4 hours to form a composite material with a carbon coating amount of 5% to 15%.

14. A negative electrode sheet, characterized in that: The invention comprises a current collector and a negative electrode active material layer coated on the current collector, wherein the negative electrode active material layer comprises the negative electrode composite material according to any one of claims 8 to 13.

15. A lithium ion battery, characterized in that: A battery cell comprising a positive electrode sheet, a separator and a negative electrode sheet stacked or wound in sequence, and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet as described in claim 13.